(untitled) (Scientific journal of the Fergana State University, 2023)
The element composition of persimmon leaves and fruits samples for the first time was studied in detail by mass spectrometry with inductively coupled plasma on ICP-MS AT 7500. A total of 42 elements were quantified in persimmon leaves and fruits. It was found that 39 elements were present in the leaves, 40 elements in the “chocolate” variety fruits and 39 elements in the lemon variety fruits (with astringent taste). The natural tendency of the amount of the element to decrease with increasing mass is shown. It has been observed that the amount of heavy elements in the fruits of the date plant is very low.